The nature of the native and the fate applied P in Two soils differing in calcium carbonate and clay contents - Hamad, Y.A; EI Mahi, Y. G; Eldoumi, F.M (Al-Mukhtar Journal of Sciences, 1996)
This laboratory study was conducted to examine the nature of the native and the fate of applied P in two semi-arid soils differing in clay and calcium carbonate contents. The soils were located about 30 Km south east of Benghazi City, Libya. Monoammonium phosphates (MAP), diamonium phosphates (DAP) and monocalcium phosphates (MCP) were applied to the two soils at the rates 30, 90 and 200 Mg P/g/ and their fates were studied after incubation at 30 +1° C and a weakly wetting and drying cycles. Solubility studies showed that both native and applied P were mainly stored as Calcium phosphates, and that the efficiency of fertilizers was comparable, except that diamonoammonium phosphate was superior regarding available P. Available P was generally associated with Caco, contents but not with clay or iron oxide contents. Significant amounts of added P were stored as organic P during incubation.